Polygonal Patterned Ground And Ancient Buried Ice On Mars And In Antarctica - Bannister, Michele T (Zenodo, 2007)
Polygonal patterned ground and buried ice are features of the permafrost environments of Earth and Mars. A detailed understanding of these periglacial features in a terrestrial environment is necessary, as it will aid future interpretation of data provided by remote study of the features on Mars. It will also provide a reference for monitoring the effects of climate change on Earth. In this study, the terrestrial context is provided by the examination of the subsurface physical properties of patterned ground and buried ice. The research is undertaken through ground-based geophysical methods in the Dry Valleys (Victoria Valley and Beacon Valley) of Antarctica. These are the most similar terrestrial sites to Mars. A 1.3 km transect profile across each valley was created using the methods of resistivity tomography, ground-penetrating radar, time-domain (transient) electromagnetism and a magnetic survey. Analysis of the data found the depth of the buried massive ice in Beacon Valley to be far greater than previously thought: over a hundred metres and across a large spatial extent. Regularly spaced, vertical features of high resistivity were interpreted as connections between the ice-cemented polygon centres and the massive ice body of Beacon Valley. Several lenses of massive ice were found in the layered permafrost sediments of Victoria Valley. The depth to the basement bedrock, inferred from the time-domain electromagnetism measurements, was over a hundred metres. This bedrock appeared to be overlain by a layer of brackish water. Regularly spaced, resistive vertical features in the near surface were interpreted as the sand wedges or cracks of the polygonal patterned ground. Due to its successful application in Victoria Valley, it is proposed that time-domain electromagnetism would be a useful geophysical method for inclusion on a future Mars mission. : GEOL 490 Project, submitted in partial fulfilment of the requirements for the degree of Bachelor of Science with Combined Honours in Astronomy and Geology at the University of Canterbury, Christchurch, New Zealand.